Kualitas Website Dan Harga Mempengaruhi Loyalitas Pelanggan Melalui Variabel Kepercayaan Di Traveloka - Hadita (Jurnal Kajian Ilmiah, 2022)
This study aims to determine the effect of website quality, price and trust on consumer loyality attitudes on purchasing airline ticket and hotels booking online at Traveloka. Sampling methode using non probability sampling with accidental sampling technique. The questionnaire was distributed online to 150 respondents. Data were analyzed using path analyzed with Amos. The results shpwed that the variables of website quality, price and trust are positive and significant to the consumer loyality on purchasing airline tickets and hotels booking online at Traveloka. The biggest variable affecting consumer loyality to words purchasing airline tickets and price variable, becouse consumer fell the price.